2008
DOI: 10.2190/ec.38.2.e
|View full text |Cite
|
Sign up to set email alerts
|

Research on Computer-Mediated Instruction for Students with High Incidence Disabilities

Abstract: In this literature review, the effects of computer-mediated instruction on the learning of students with mild and moderate disabilities are synthesized from 1996 onward that extends our previously published synthesis for the period 1987-1995. Empirically based findings are reviewed and discussed in the basic skills areas of reading, writing, and mathematics, as well as in the content areas of social studies and science. Results are interpreted and discussed regarding traditional teaching methodologies in speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 48 publications
1
24
0
3
Order By: Relevance
“…Our final step was an examination of previously published systematic reviews of the literature for interventions that included graphic organizers and/or technology across all academic subjects (Boon et al., ; Dexter & Hughes, ; Dexter et al., ; Gajria et al., ; Kim et al., ; Stetter & Hughes, ; Wanzek et al., ), including mathematics (Fitzgerald et al., ). These articles were searched to determine if any of the included studies integrated a computer‐based graphic organizer.…”
Section: Methodsmentioning
confidence: 99%
“…Our final step was an examination of previously published systematic reviews of the literature for interventions that included graphic organizers and/or technology across all academic subjects (Boon et al., ; Dexter & Hughes, ; Dexter et al., ; Gajria et al., ; Kim et al., ; Stetter & Hughes, ; Wanzek et al., ), including mathematics (Fitzgerald et al., ). These articles were searched to determine if any of the included studies integrated a computer‐based graphic organizer.…”
Section: Methodsmentioning
confidence: 99%
“…Ayrıca bu süreçte, BEP geliştirme, BÖP hazırlama, öğretim yöntemini belirleme ve bu yönteme göre içeriği şekillendirme gibi pedagoji bilgisinin ne kadar önemli olduğu görülmektedir. Alanyazında belirtildiği gibi "teknolojiyi kullanabilir olmanın teknoloji entegrasyonunu sağlıklı bir şekilde yapabilir" anlamına gelmediği bu araştırmada da belirlenmiştir (Edyburn, 1998;Fitzgerald ve Koury, 2008;Girgin vd., 2011;Kabakçı-Yurdakul ve Odabaşı, 2013;King-Sears ve Evmenova, 2007;Liu vd., 2013;Marino, Sameshima ve Beecher, 2009;Smith ve Okolo, 2010;Tournaki ve Lyublinskaya, 2015;United Nations Educational Scientific and Cultural Organization, 2006, s. 115). Ayrıca, öğrencilerin öğrenmelerine olumlu katkıları olacak içeriklerin geliştirilmesi, etkili olduğu bilinen teknolojik araçların sınıfa yerleştirilmesinin yanında bu araçların öğretim etkinliklerinin rutin bir parçası haline getirilmesi teknoloji entegrasyonunda dikkate alınması gereken önemli bir detay olarak vurgulanabilir.…”
Section: Teknolojinin Programa Entegrasyonuunclassified
“…Bu bulgu alanyazında teknolojinin zihin yetersizliği olan öğrencilerin akademik becerileri edinmede etkili olduğunu gösteren araştırmaların bulguları ile örtüşmektedir (Campigotto vd., 2013;Fitzgerald ve Koury, 2008;Liu vd., 2013;Sheriff ve Boon, 2014). Araştırmanın bulguları, öğrencilerin öğrendikleri yeni bilgileri günlük yaşamlarında uygun bir biçimde kullandıklarını göstermiştir.…”
Section: Fen Ve Teknoloji Dersi öğRetim Etkinliklerinde Teknoloji Kulunclassified
See 1 more Smart Citation
“…Blischak and Schlosser's (2003) review investigated the use of word processing software with synthetic speech capabilities and found that computer applications using this software is a potential means for improving the spelling and frequency of spontaneous utterances of individuals with ASD. Fitzgerald, Koury, and Mitchem (2008) reviewed reported improvements in academics (i.e., reading, mathematics, writing, social studies, and science) as a result of using CBI by children with mild or high disabilities. Finally, Ramdoss et al (2011) developed a systematic review of CBI for improving communication skills of children with ASD.…”
Section: Using Computers In Asd Interventionsmentioning
confidence: 99%